Pengembangan Media Pembelajaran Audio Visual Tema Daerah Tempat Tinggalku di Sekolah Dasar - Eris Oktaria Umami; Chumi Zahroul Fitriyah; Zetty Finnaly (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
This research was conducted in class IV of Kepatihan Elementary School 01 Jember with 38 research subjects. The purpose of this study is to describe the process and find out the results of the development of audio visual as learning media with the theme of my residence area on the 4th grade students at SDN Kepatihan 01 Jember. This type of research is research and development. Type model uses ADDIE (Analyze, Design, Development, Implementation, Evaluation). The data analysis technique in this study used a validation sheet of audio visual learning media by the media expert validator and the material expert validator, and student learning outcomes assessment sheets and student responses. The results of the research data analysis showed the effectiveness of the results of the validation carried out by the two validators obtained results of 81,7 while the results obtained from the student learning outcomes test were 94,7% and student responses amounted to 73,7% so that it can be concluded that the audio-visual learning media has very fasible and effective criteria try out. Keywords: Audio visual, learning media, elementary school